Expectations-driven liquidity traps: Implications for monetary and fiscal policy - Taisuke Nakata; Sebastian Schmidt (European Central Bank (ECB), 2019)
We study optimal monetary and fiscal policy in a New Keynesian model where occasional declines in agents' confidence can give rise to persistent liquidity trap episodes. Unlike in the case of fundamental-driven liquidity traps, there is no straightforward recipe for mitigating the welfare costs and the systematic in ation shortfall associated with expectations-driven liquidity traps. Raising the in ation target or appointing an in ation-conservative central banker improves in ation outcomes away from the lower bound but exacerbates the shortfall at the lower bound. Using government spending as an additional policy tool worsens stabilization outcomes both at and away from the lower bound. However, appointing a policymaker who is sufficiently less concerned with government spending stabilization than society can eliminate expectations-driven liquidity traps altogether.
Keywords: E52; E61; E62; 330; Effective Lower Bound; Sunspot Equilibria; Monetary Policy; Fiscal Policy; Discretion; Policy Delegation